INFLUENCE OF INTEGRATED USE OF HERBICIDE AND ALLELOPATHIC AQUEOUS EXTRACTS ON WEEDS AND GROUNDNUT CROP PERFORMANCE - S. Hussain; F. U. Hassan (Journal of Animal and Plant Sciences, 2015)
Allelopathicaqueous extracts can be used in integration with herbicides for controlling weeds in field crops. Effect of allelopathic water extracts and their mixtures with haloxyfop 10.8 EC was investigated to control weeds in groundnut and subsequent effects on crop yield through field experiments executed under rainfed conditions during 2009-2011. Treatments included weedy check, hand weeding, haloxyfop 10.8 EC @ 108 g a.i. ha-1, barley water extract, brassica water extract, barley+brassica water extract and its combinations with 25, 50 and 75% rates of haloxyfop 10.8 EC arranged in randomized complete block design replicated four times. Results demonstrated that mixture of allelopathic extracts with lower doses of haloxyfopreduced density and dry weights of weed species by 9-58% and 10-52%, respectively. Haloxyfop 10.8 EC @ 108 g a.i. ha-1 reduced these parameters upto59% and 54%. Hand weeding decreased density and dry weight of weed species by 50-88%. Statistically similar yields were obtained from allelopathic water extracts combined with reduced rates of herbicide and its full dose. The maximum pods yield was recorded from hand weedingbut the maximum net benefits were achieved from barley and brassica water extracts mixed with 75% rates of haloxyfop 10.8 EC. Crop yield and net benefit showed inverse relationship with weed density and total dry biomass of weeds during both the years. Barley and brassicaaqueous extracts with lower rates of haloxyfop 10.8 EC may be used to manage weeds economically in groundnut crop under rainfed conditions.
Keywords: weeds; water extracts; allelopathy; groundnut; barley; brassica